Development of E-Modules Based on Articulate Storyline 3 to Improve Accounting Cycle Learning Outcomes - Laurensius Reinald Diansilves Due; Siswanto; Ahmad Fadhil Imran (Jurnal Pendidikan Indonesia, 2023)
Teachers as the main actors of learning often use learning methods that are not suitable in supporting student learning outcomes. This research was made in order to analyze the right method to improve student learning outcomes through teaching materials in the form of e-modules based on Articulate Storyline 3 on learning the accounting cycle of service companies. This research is a type of RnD research with a model that has been developed by Borg & Gall. Data was collected from the assessment of two experts through expert validation sheets, as well as responses from two teachers and 99 students through a student response questionnaire. The results of the research gave birth to a product in the form of an e-module based on the storyline of articulation 3 which can be accessed by teachers and students using HTML. This product is suitable for use by teachers with the right method and has implications for improving student learning outcomes.